Prompt and non-prompt $J/\psi $ elliptic flow in Pb+Pb collisions at $\sqrt{s_{_\text {NN}}} = 5.02$ Tev with the ATLAS detector - ATLAS collaboration (2924 authors) (2018)
The elliptic flow of prompt and non-prompt $J/\psi $ was measured in the dimuon decay channel in Pb+Pb collisions at $\sqrt{s_{_\text {NN}}}=5.02$   $\text {TeV}$ with an integrated luminosity of $0.42~\mathrm {nb}^{-1}$ with the ATLAS detector at the LHC. The prompt and non-prompt signals are separated using a two-dimensional simultaneous fit of the invariant mass and pseudo-proper decay time of the dimuon system from the $J/\psi $ decay. The measurement is performed in the kinematic range of dimuon transverse momentum and rapidity $9<p_\mathrm {T}<30$   $\text {GeV}$ , $|y|<2$ , and 0–60% collision centrality. The elliptic flow coefficient, $v_2$ , is evaluated relative to the event plane and the results are presented as a function of transverse momentum, rapidity and centrality. It is found that prompt and non-prompt $J/\psi $ mesons have non-zero elliptic flow. Prompt $J/\psi $ $v_2$ decreases as a function of $p_\mathrm {T}$ , while for non-prompt $J/\psi $ it is, with limited statistical significance, consistent with a flat behaviour over the studied kinematic region. There is no observed dependence on rapidity or centrality.